2001
DOI: 10.1046/j.1365-2605.2001.00280.x
|View full text |Cite
|
Sign up to set email alerts
|

Aneuploidy in spermatozoa of infertile men with teratozoospermia

Abstract: Recent studies have shown that aneuploidy in spermatozoa of infertile men with poor semen quality is increased. The purpose of this study was to determine whether poor sperm morphology is associated with the incidence of spermatozoa with numerical chromosome abnormalities. Semen samples from 20 infertile teratozoospermic men were studied using multicolour fluorescence in situ hybridization (FISH). Men were divided into four groups according to the proportion of normal sperm morphology: infertile men with <10% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
20
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 63 publications
6
20
2
Order By: Relevance
“…However, a recent publication seemed to minimize the impact of altered spermiogenesis on chromosome topography (Ioannou et al, 2011). Secondly, oligozoospermia (Rives et al, 1999;Vegetti et al, 2000;Calogero et al, 2001;Tempest & Griffin, 2004), asthenozoospermia (Vegetti et al, 2000;Tempest & Griffin, 2004) and teratozoospermia (Calogero et al, 2001;Harkonen et al, 2001;Machev et al, 2005) have been related to sperm aneuploidy. Confusingly, sperm aneuploidy has been associated with modification of chromosome localization in sperm heads: Olszewska et al (2008) demonstrated disturbances in the centromere area in sperm nuclei of infertile patients with an increased level of aneuploidy compared with fertile males; in sperm cells of infertile patients with an increased level of aneuploidy, 'some differences in the preferential longitudinal centromere positioning between sperm nuclei with hyperhaploidic karyotype (n + 1) vs. normal karyotype (n)' were observed.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent publication seemed to minimize the impact of altered spermiogenesis on chromosome topography (Ioannou et al, 2011). Secondly, oligozoospermia (Rives et al, 1999;Vegetti et al, 2000;Calogero et al, 2001;Tempest & Griffin, 2004), asthenozoospermia (Vegetti et al, 2000;Tempest & Griffin, 2004) and teratozoospermia (Calogero et al, 2001;Harkonen et al, 2001;Machev et al, 2005) have been related to sperm aneuploidy. Confusingly, sperm aneuploidy has been associated with modification of chromosome localization in sperm heads: Olszewska et al (2008) demonstrated disturbances in the centromere area in sperm nuclei of infertile patients with an increased level of aneuploidy compared with fertile males; in sperm cells of infertile patients with an increased level of aneuploidy, 'some differences in the preferential longitudinal centromere positioning between sperm nuclei with hyperhaploidic karyotype (n + 1) vs. normal karyotype (n)' were observed.…”
Section: Discussionmentioning
confidence: 99%
“…While the majority report an association between increased disomy 1 levels, several (Miharu et al, 1994;Guttenbach et al, 1997;Harkonen et al, 2001) found no evidence of such an increase. Guttenbach et al (1997) examined 45 males with varying compromised semen parameters (and 8 controls) reporting no significant difference between them (0.13 and 0.12 %, respectively).…”
Section: Chromosomes 1-5 (Groups a And B)mentioning
confidence: 96%
“…Association between morphological sperm deformities and sperm chromosomal abnormalities has been investigated extensively but the results were controversial. Most of the studies showed that teratozoospermia, like other forms of abnormal semen profiles (asthenozoospermia, oligozoospermia), is a marker of elevated sperm aneuploidy [21][22][23][24][25][26][27][28]. Indeed, sperm of isolated teratozoospermic men have shown higher rates of chromosomal abnormalities than that of fertile controls [24,26,28].…”
Section: Discussionmentioning
confidence: 99%